Species of Branchiomma (Polychaeta: Sabellidae) from the Caribbean Sea and Pacific coast of Panama - Tovar-Hernández, María Ana; Knight-Jones, Phyllis (Zootaxa, 2006)
Six species of Branchiomma Kölliker (1858) from the Caribbean Sea and Pacific coast of Panama are described or redescribed, and a key for their identification is provided. All six have dorsal collar margins widely separate and thoracic uncini with few rows of teeth on the uncinal crests. Branchiomma nigromaculatum (Baird, 1865), B. bairdi (McIntosh, 1885) and B. conspersum (Ehlers, 1887) are redescribed from type material and designated lectotypes. Each has at least two pairs of macrostylodes, stylodes which are longer than their neighbouring pairs, flanking the middle area of each crown radiole. Those of B. nigromaculatum, a large-bodied species, are only twice as long as their neighbours, whereas those of the other two smaller species are more than four times as long. Stylodes are sub-digitiform in B. nigromaculatum, strap-like in B. bairdi and tongue–like in B. conspersum. Branchiomma nigromaculatum differs from B. bairdi and B. conspersum in having thoracic uncini with one row of large teeth on each thoracic uncinal crest (side view), covering less than a quarter of the crest length. Branchiomma curtum (Ehlers, 1901) is described as a new record for the Caribbean Sea. It has a few, small, digitiform stylodes and thoracic uncini with three rows of teeth, covering a half of the crest length. Branchiomma coheni is described as a new species from Naos, Pacific coast of Panama. It has broad, flattened, foliose stylodes, forming fairly even gradations of size throughout the radiole length, and thoracic uncini with two rows of teeth on the crest. Branchiomma iliffei is described as a new species from Bahamas. It has many, narrow, stylodes of similar size, unusually large radiolar eyes, a short crown (a quarter of the body length), short dorsal lips (a quarter of the crown length), long triangular ventral lappets and three rows of teeth, covering about one half of the crest length.